Pulmonary alterations in cocaine users - Mário Terra Filho; Chen Chin Yen; Ubiratan de Paula Santos; Daniel Romero Muñoz (São Paulo Medical Journal)
CONTEXT: Brazilian researchers have recently recognized a marked increase in the number of people using abusable drugs and the consequences of this habit. It has become a major public health problem in a potentially productive segment of the general population. In the last few years, several medical articles have given special emphasis to pulmonary complications related to cocaine use. This review is based on this information and experience acquired with groups of cocaine users. OBJECTIVE: To present to physicians the pulmonary aspects of cocaine use and warn about the various effects this drug has on the respiratory system, stressing those related to long-term use. DESIGN: Narrative review. METHOD: Pulmonary complications are described. These may include infections (Staphylococcus aureus, pulmonary tuberculosis, acquired immunodeficiency syndrome/aids, etc.), aspiration pneumonia, lung abscess, empyema, septic embolism, non-cardiogenic pulmonary edema, barotrauma, pulmonary granulomatosis, bronchiolitis obliterans and organizing pneumonia, pneumonitis and interstitial fibrosis, pneumonitis hypersensitivity, lung infiltrates and eosinophilia in individuals with bronchial hyperreactivity, diffuse alveolar hemorrhage, vasculitis, pulmonary infarction, pulmonary hypertension and alterations in gas exchange. It is concluded that physicians should give special attention to the various pulmonary and clinical manifestations related to cocaine use, particularly in young patients.